A Study of Using English for Communication to Enhance the Tourism Information by Staffs at The National Museum in Luangprabang Lao PDR - BOUNTHAVONG, Oudalon; THOR, Maiher (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The objective of this study were to study using English for communication to enhance the tourism information at Luangprabang National Museum, and to study tourists’ satisfaction level of using English for communication to enhance the tourism information at Luangprabang National Museum. The sample consisted of 30 staff who work at Luangprabang National Museum, Luangprabang, Laos, and 25 tourists. They were selected using cluster random sampling. This study was quantitative research. The research instrument was questionnaires that included 15 questions for staff and 12 questions for tourists. The collection data lasted 1 week, the mean, percentage, standard deviation and were used for data analysis. The findings of this study were as follows: The using English for communication to enhance the tourism information was at good level that mean the staffs can use English for communication to enhance on restrictions such as: do not touch the ancient objects, response tourists’ asking and others, because almost of them get diploma or bachelor of English from Colleges and Universities. The tourists’ satisfaction level to the using English for communication to enhance the tourism information was at high level because of the tourists get information clearly from staff with happiness and good service at Luangprabang National Museum.